Varenicline for smoking cessation: A review of the literature - Kaur, Kirandeep (Elsevier, 2009)
Background: Smoking is the leading preventable risk to human health. Various agents have been used to promote smoking cessation, but none has had long-term efficacy. Varenicline, a new nicotinic ligand based on the structure of cytosine, was approved by the US Food amd Drug Administration for use as a smoking cessation aid. Objectives: The aims of this review were to provide an overview on the mechanism of action and preclinical and clinical data of the new drug, varenicline, and to discuss the current and future impact of varenicline as a treatment for smoking cessation. Methods: MEDLINE, BIOSIS, and Google scholar databases were searched (March 1, 2007–July 1, 2008) using the terms varenicline, smoking cessation, and nicotinic receptors. Full-text articles in English were selected for reference, and articles presenting the mechanism of action, pharmacokinetics, and data from preclinical and clinical trials were included. Results: The initial literature search yielded 70 papers. A total of 20 articles fulfilled the inclusion criteria. Varenicline, an α(4)β(2) nicotinic acetylcholine receptor partial agonist, inhibits dopaminergic activation produced by smoking and decreases the craving and withdrawal syndrome that accompanies cessation attempts. In Phase III clinical trials, the carbon monoxide-confirmed 4-week continuous abstinence rates were significantly higher with varenicline than with buproprion sustained release or placebo for weeks 9 through 12. Varenicline has been found to be well tolerated, with nausea being the most commonly reported (28.1%) adverse event. Conclusions: Varenicline is the first drug for smoking cessation that has been found to have significant effectiveness in long-term relapse prevention (up to 52 weeks). Varenicline, with its unique profile of agonist and antagonist properties, increased cessation rates (both short- and long-term) compared with both placebo and bupropion sustained release.